Exam Ref AZ-800 administering Windows Server hybrid core infrastructure - Thomas, Orin 1973- (Pearson Education, Inc., 2023)
Prepare for Microsoft Exam AZ-800 and demonstrate your real-world mastery of designing, implementing, and managing Windows Server core infrastructure in a hybrid cloud environment. Designed for professionals with Windows Server experience in on-premises, hybrid, and Azure environments, this Exam Ref focuses on the critical thinking and decision-making acumen needed for success at the Microsoft Certified: Windows Server Hybrid Administrator Associate level. Exam AZ-800 focuses on knowledge needed to deploy and manage AD DS domain controllers; configure and manage multi-site, multi-domain, and multi-forest environments; create and manage AD DS security principals; implement and manage hybrid identities; manage Windows Server via domain group policies and in hybrid environments; manage Windows Servers and workloads via Azure services; manage Hyper-V, guest VMs, and Azure VMs running Windows Server; create and manage containers; implement on-premises and hybrid name resolution; manage IP addressing and implement network connectivity; configure and manage Azure File Sync and Windows Server fi le shares; and configure Windows Server storage. Passing this exam and Exam AZ-801 (Configuring Windows Server Hybrid Advanced Services) fulfills your requirements for the Microsoft Certified: Windows Server Hybrid Administrator Associate credential.
Includes index
Keywords: Microsoft Windows server -- Study guides -- Examination; Microsoft Windows server; Study guides